Didactical Process of Religious Moderation Toward Inclusive Society in Rewwin Housing Sidoarjo Jatim (International Journal of Interreligious and Intercultural Studies, 2025)
Humans are social creatures that cannot be separated from socializing life. After living nomads, humans decided to settle down and colonize and form a culture, quoting Harari (2022: 1) Homo sapiens began to form a more complicated structure called culture, from this human culture is called history. The growth of culture coexists with the growth of religion. Religion for humans is expected to be able to explore all the potential of humanity so that it can foster self-awareness. But in reality, religion triggers conflict. Today, violence in the name of religion is very widespread. Quoting the coil (2024), there was a dissolution of worship that led to beatings in Tangsel, which caused commotion in the name of religion. One form of individual or group awareness of cultural diversity is through the didactic process of religious moderation. The cultivation of human values through religious moderation is expected to produce individuals who have an attitude of tolerance. When there are various riots and acts of violence that have religious nuances, it is alleged that religious education fails to form empathetic and tolerant people. Religious education is not only carried out in formal spaces, informal and non-formal are very important in character building. One of the non-formal religious education conducted in Rewwin Sidoarjo Settlement, which is inhabited by people from various religious, ethnic and cultural backgrounds. Despite being a heterogeneous community, there has never been any friction or conflict in the last five years. This phenomenon prompted the author to examine the didactic process of religious moderation towards an inclusive society in Rewwin housing estate in Sidoarjo, East Java. This article provides answers to the questions: 1) Why the strengthening of religious moderation, the didactic reason of religious moderation towards an inclusive society is instilled in the community in Rewwin Sidoarjo residential neighborhood. 2) The didactic process of religious moderation towards an inclusive society is instilled in the community in the Rewwin Sidoarjo residential neighborhood, and 3.) The implications of the didactic process of religious moderation towards an inclusive society on social, cultural and religious life in the community in the Rewwin Sidoarjo residential neighborhood. The theories used are 1) Constructivistic Theory, Jean Peaget. 2) Social Learning Theory, Albert Bandura. 3) Stuart Hall's Reception Theory, this article uses a qualitative research model with a purposive sampling interview approach, where Rewwin housing residents are key informants who answer the quality of moderation. The results of the analysis show that there are positive practices carried out as a strengthening of religious moderation in the community in the Rewwin Sidoarjo housing environment. Religious moderation is a demand for every Indonesian citizen to achieve the consientization of life in the frame of diversity.